The Role of Fetal Health Locus of Control and Obedience in Traditional Pregnancy Care Toward Low Birth Weight (LBW) Occurence in Kupang - Simplicia Maria Anggrahini; Hari Basuki Notobroto; Rika Subarniati Triyoga (Health Notions, 2018)
Prevalence and mortality due to low birth weight (LBW) is still get a mark in Kupang. The multifactorial causes of LBW, can be grouped into these factors: physical and social environment, mother, fetus, placenta-umbilical cord, and health services. From maternal factors, there are subfactors of maternal characteristics, knowledge of pregnancy, maternal health status, and behavior in caring the pregnancy. Maternal behavior may be in the form of obedience in traditional pregnancy care, which may lead to LBW. Most studies on LBW risk factors are related to clinical medical factors. The purpose of this study was to predict the role of fetal health locus of control and obedience in traditional pregnancy care, toward LBW occurrence. This study was an analitic observational with case-control design, included 50 mothers who gave birth to LBW and 50 mothers who gave birth to normal babies, through interviews and tracing of maternal and infant medical records. Research was done in RSUD Prof. DR. W.Z. Johannes, RSIA Dedari and 2 basic emergency obstetric and newborn care (BEmONC) public health center. Data analysis done using SmartPLS 3.2.6. The results of the study proved that obedience to traditional pregnancy care was a mediator of the occurrence of LBW, whereas fetal health locus of control was not. Obedience to traditional pregnancy care in the form of non-standardize antenatal care and continued heavy workload during pregnancy, had been shown to cause LBW. This research also found 2 pathway models of LBW occurence: 1) Mother's characteristic (education level, mother's income, total of family income) influence to LBW occurence through variables: pregnancy knowledge, perceived behavioral control, and obedience to traditional pregnancy care. 2) Maternal characteristics have an effect on the occurence of LBW through obedience to traditional pregnancy care. Keywords: Low birth weight, Obedience, Traditional pregnancy care, Fetal health locus of control